2009
DOI: 10.1007/s00204-009-0425-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and apoptotic changes in primary cultures of rat proximal tubular cells exposed to lead

Abstract: Lead is a known nephrotoxic element. In this study, primary cultures of rat proximal tubular (rPT) cells were treated with different concentrations of lead acetate (0.25, 0.5 and 1 microM) to investigate its cytotoxic mechanism. A progressive loss in cell viability together with a significant increase in the number of apoptotic and necrotic cells and lactate dehydrogenase release were seen in the experiment. Simultaneously, elevation of reactive oxygen species levels and intracellular [Ca(2+)]i, depletion of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 41 publications
3
64
0
Order By: Relevance
“…Besides that hypogonadism is a clinical condition in which low levels of serum testosterone are found in association with specific signs and symptoms. When hypogonadism occurs in an older man, the condition is often called andropause or androgen deficiency of the aging male or late onset hypogonadism [16]. Previous study showed that castration increased lipid peroxidation and consequently reduced glutathione in both liver and kidney [17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that hypogonadism is a clinical condition in which low levels of serum testosterone are found in association with specific signs and symptoms. When hypogonadism occurs in an older man, the condition is often called andropause or androgen deficiency of the aging male or late onset hypogonadism [16]. Previous study showed that castration increased lipid peroxidation and consequently reduced glutathione in both liver and kidney [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been reported that L.A. causes mitochondrial damage, uncoupling of the respiratory chain and cell death [16]. Another histological indication of lead toxicity in the kidney is the karyomegaly of tubular cells [27].…”
Section: Kidneymentioning
confidence: 99%
“…A number of studies have revealed that lead exposure is capable of inducing cell death in a variety of cell types (Fox et al, 1998;Cheng et al, 2002;Wang et al, 2009). Even though the mechanisms relevant to lead-induced cell death have yet to be fully elucidated, some have implied a relationship between oxidative stress and cell death in lead-induced cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The reason was consumption of plants containing high levels of selenium. Symptoms of selenosis in humans are similar to those observed in the horses of Fort Randall: fatigue, hair loss, gastrointestinal symptoms, liver damage, and neurological and CNS symptoms, including aggressiveness.Selenium (BrozmanovĂĄ et al 2010;Valdiglesias et al 2010; Grotto et al 2009a, b) and oxidative as well as antioxidative mechanisms in general (Bolt and Hengstler 2010;Nishimura et al 2010;Cederbaum et al 2009; Grotto et al 2009a, b;Hewitt et al 2007;Wang et al 2009;Glahn et al 2008) represent cutting-edge topics in toxicology. Therefore, the editors are pleased that Cristina W Nogueira and Joao BT Rocha from Santa Maria University in Brazil have accepted our invitation to contribute a comprehensive review on the pharmacology and toxicology of selenium and organoselenium compounds (Nogueira and Rocha 2011).…”
mentioning
confidence: 99%